Controlling for race/ethnicity: a comparison of California commercial health plans CAHPS scores to NCBD benchmarks - Lopez Rebeca A; Hughes Susan; Zweifler John (BMC, 2010)
Abstract Background Because California has higher managed care penetration and the race/ethnicity of Californians differs from the rest of the United States, we tested the hypothesis that California's lower health plan Consumer Assessment of Healthcare Providers and Systems (CAHPS®) survey results are attributable to the state's racial/ethnic composition. Methods California CAHPS survey responses for commercial health plans were compared to national responses for five selected measures: three global ratings of doctor, health plan and health care, and two composite scores regarding doctor communication and staff courtesy, respect, and helpfulness. We used the 2005 National CAHPS 3.0 Benchmarking Database to assess patient experiences of care. Multiple stepwise logistic regression was used to see if patient experience ratings based on CAHPS responses in California commercial health plans differed from all other states combined. Results CAHPS patient experience responses in California were not significantly different than the rest of the nation after adjusting for age, general health rating, individual health plan, education, time in health plan, race/ethnicity, and gender. Both California and national patient experience scores varied by race/ethnicity. In both California and the rest of the nation Blacks tended to be more satisfied, while Asians were less satisfied. Conclusions California commercial health plan enrollees rate their experiences of care similarly to enrollees in the rest of the nation when seven different variables including race/ethnicity are considered. These findings support accounting for more than just age, gender and general health rating before comparing health plans from one state to another. Reporting on race/ethnicity disparities in member experiences of care could raise awareness and increase accountability for reducing these racial and ethnic disparities.